2014
DOI: 10.1007/s13246-014-0261-1
|View full text |Cite
|
Sign up to set email alerts
|

Direct and pulsed current annealing of p-MOSFET based dosimeter: the “MOSkin”

Abstract: Contemporary radiation therapy (RT) is complicated and requires sophisticated real-time quality assurance (QA). While 3D real-time dosimetry is most preferable in RT, it is currently not fully realised. A small, easy to use and inexpensive point dosimeter with real-time and in vivo capabilities is an option for routine QA. Such a dosimeter is essential for skin, in vivo or interface dosimetry in phantoms for treatment plan verification. The metal-oxide-semiconductor-field-effect-transistor (MOSFET) detector is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…It is a real‐time dosimeter and has good characteristics linearity and decent reproducibility 53 , 54 . MOS kin detector has always been used in its linear dose range by using current annealing technique 60 , 61 for recovery of its initial threshold values after about 30 Gy accumulated dose that warrants its linearity. However, care needs to be taken to minimize measurement uncertainties, such as voltage creep‐up effect that could introduce up to 2% error in a typical clinical dose of 2 Gy (62) .…”
Section: Methodsmentioning
confidence: 99%
“…It is a real‐time dosimeter and has good characteristics linearity and decent reproducibility 53 , 54 . MOS kin detector has always been used in its linear dose range by using current annealing technique 60 , 61 for recovery of its initial threshold values after about 30 Gy accumulated dose that warrants its linearity. However, care needs to be taken to minimize measurement uncertainties, such as voltage creep‐up effect that could introduce up to 2% error in a typical clinical dose of 2 Gy (62) .…”
Section: Methodsmentioning
confidence: 99%
“…The MOSFET needs to be replaced when the upper limit of linearity is achieved. Although, recently, the possibility of MOSFET reuse after recovering for a certain period of time at room or elevated temperature [22] or by current annealing [23] has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Once the upper limit of linearity is achieved, the RADFETs need to be replaced. However, recent studies have shown that such RADFETs can be recovered for reuse by storing at room or elevated temperature for a sufficient time [22], [23] or by annealing with current [24], [25].…”
Section: Introductionmentioning
confidence: 99%